HUBUNGAN KEPATUHAN PENGOBATAN DENGAN KEKAMBUHAN PASIEN PPOK DI RUANG ASOKA RSUD Dr. HARJONO S. PONOROGO - Ganda Ardiansyah; Bayu Sigit Wahono (JURNAL SABHANGA, 2026)
Acute exacerbations, more commonly known as relapses of ChronicObstructive Pulmonary Disease (COPD), are common. Poor medication adherence iscommon and results in increased morbidity, mortality, and decreased quality of life.Thisstudy aims to determine the relationship between medication adherence and relapse in COPDpatients in the Asoka Ward of Dr. Harjono S. Ponorogo Regional General Hospital